2020
DOI: 10.1371/journal.pone.0230978
|View full text |Cite
|
Sign up to set email alerts
|

Associations between infant and young child feeding practices and acute respiratory infection and diarrhoea in Ethiopia: A propensity score matching approach

Abstract: Background Acute respiratory infection (ARI) and diarrhoea are the leading causes of childhood morbidity and mortality in Ethiopia. Understanding the associations between infant and young child feeding (IYCF) and ARI and diarrhoea can inform IYCF policy interventions and advocacy in Ethiopia. This study aimed to investigate the relationship between IYCF practices and ARI and diarrhoea in Ethiopian children. Methods This study used the Ethiopia Demographic and Health Survey (EDHS) data for the years 2000 (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 67 publications
(126 reference statements)
4
24
1
Order By: Relevance
“…These events have important implications for low agricultural production, food insecurity and childhood undernutrition. Additionally, long-lasting high population pressures and deforestation, as well as a high variability in rainfall in the region are likely to have affected land preservation and suitability for crop production and animal grazing [ 5 , 71 ]. Geographically targeted nutritional interventions have the potential to accelerate reductions in childhood stunting through improvement and optimization of resource allocation for programs and services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These events have important implications for low agricultural production, food insecurity and childhood undernutrition. Additionally, long-lasting high population pressures and deforestation, as well as a high variability in rainfall in the region are likely to have affected land preservation and suitability for crop production and animal grazing [ 5 , 71 ]. Geographically targeted nutritional interventions have the potential to accelerate reductions in childhood stunting through improvement and optimization of resource allocation for programs and services.…”
Section: Discussionmentioning
confidence: 99%
“…In this age group, appropriate nutrition, psychosocial interactions and a built environment are essential to meet childhood developmental and nutritional requirements. However, early years nutritional deficiencies (that is, becoming underweight, stunted or wasted) are associated with short- and long-term adverse consequences among children [ 1 , 2 , 5 , 6 , 7 , 8 ]. Suppressed immunity, increased risk of morbidity and mortality, and lower school performance have been reported in children with stunting [ 1 , 2 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism, as well as the benefits of how breastfeeding increases child survival, are well documented in the scientific literature [ 7 ]. Breastfeeding prevents the introduction of potentially contaminated prelacteal foods, provides newborns with colostrum (rich in a variety of nutrients and immunoglobulins) and protects against diarrheal diseases and respiratory tract infection [ 7 , 8 , 9 , 10 , 11 , 12 ]—two leading causes of preventable under-five-years deaths in Bangladesh [ 13 ]. Numerous research from Bangladesh has identified the determinants of breastfeeding (BF) practices among mothers of all age groups [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] Furthermore, exclusive breastfeeding until 6 months of age played a beneficial role in minimizing the risk of children suffering from ARI. [ 21 22 23 ]…”
Section: Introductionmentioning
confidence: 99%